On how RE Teachers Address the Sometimes Conflicting Tasks of Conveying Fundamental Values and Facilitating Critical Thinking - Niclas Lindström; Lars Samuelsson (Athens Institute for Education and Research, 2022)
Teachers in the non-confessional Swedish subject religious education have conflicting responsibilities to convey values and facilitate critical thinking. The research regarding these responsibilities has often been considered a theoretical problem and the discussion has concerned theoretical solutions. However, the problem is not only theoretical. It is in fact also a practical problem that many teachers frequently encounter. The overall aim of this paper is thus to draw attention to these conflicting responsibilities as a practical problem that teachers face and are expected to solve in their pedagogical practices. In line with this aim, a number of qualitative research interviews were conducted with experienced religious education teachers, who are considered to have a particular responsibility for moral education in the Swedish school system. The purpose of the interviews was to investigate how they relate to their sometimes conflicting responsibilities and consequently make an empirically informed contribution to the debate. This is an important task since there are no official guidelines on how teachers are to balance these responsibilities in their pedagogical practices.